Resolusi Konflik Internal Subak Taman Desa Taman Kecamatan Abiansemal Kabupaten Badung - AGUS ANANDA WIBAWA; I DEWA PUTU OKA SUARDI; I GEDE SETIAWAN ADI PUTRA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
Internal Conflict Resolution in Subak Taman, Taman Village, Abiansemal District, Badung Regency Subak is an organization that oversees farmers to regulate irrigation, in its activities Subak cannot avoid problems in the form of conflict. Internal conflicts within the subak organization can be triggered by various factors, namely water scarcity and weak coordination between tempek to distribute water resources. Various conflicts that can arise in subak as a consequence of interaction between individuals in the organization, in this case farmers are members of the subak, it is very necessary to handle conflicts that can be applied in the form of management of any problems that arise from the subak organization. This study aims to determine the conflicts that occur in Subak Taman and the conflict resolutions taken to overcome these internal conflicts. This research was conducted with a qualitative descriptive analysis using primary and secondary data. Data were collected through in-depth interviews, observations, documentation studies and literature studies. The results showed that the conflicts that occurred in Subak Taman, Taman Village, Abiansemal District, Badung Regency were lack of irrigation water, work situations where there was blurring of task boundaries, communication failures, cropping patterns and cropping schedules, irrigation water pollution, and individual characteristics, namely differences. traits and personalities and differences in values and needs. Conflict resolution carried out in Subak Taman is by the methods of cooperation (cooperation), avoidance, competition, compromise, accommodation, domination, and problem solving. From the results of the study it can be concluded that there are six internal conflicts that occur in Subak Taman and conflict resolution is carried out using seven methods. The results of this study are expected to be a reference for those who need it.